Collaborative requirements elicitation to foster shared understanding - Stynes, Anthony Paul (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2015)
Fostering shared understanding of how to support organisational change involves a complex interaction of stakeholders in order to achieve alignment of business processes and IT infrastructure. Collaboration and communication among stakeholders will determine the success of any organisational change initiative. The quality of alignment between the business processes and IT infrastructure will determine the business value of that organisational change. Achieving a strong alignment requires a combination of appropriate requirement elicitation techniques to gain an understanding of the business requirements. New approaches to collaborative requirements elicitation that fosters shared understanding amongst stakeholders need to address the issue of IT alignment. The contribution of this thesis to the area is an innovative collaborative requirements elicitation framework that introduces a novel combination of collaboration, communication, prototyping and modelling techniques in a manner that differs significantly from current collaborative requirement elicitation frameworks. This thesis presents the design of the theoretical framework that comprises of a process model with four activities. The thesis also describes the design of a support tool that implements the two central activities of the process model. In order to determine the extent shared understanding was fostered, the framework was evaluated in a case study of a business process for the roll out of the IT software image at a third level educational institution. The evaluation involved two experiments by stakeholders that elicited requirements for aligning the business process of the institution with an IT infrastructure. Statistical analysis showed that the collaborative requirement elicitation framework fostered shared understanding in the case study, through increases in communication and increases in stakeholder’s positive experience with collaboration. Shared understanding is also manifested in the creation of three knowledge representation artefacts namely, requirements model, IT infrastructure model, and a business process model. Statistical analysis also showed that the IT infrastructure model has the potential to represent a realistic solution. The framework will be useful to requirements engineers and business analysts that work on designing and implementing business processes. It provides them with a set of instructions and a support tool that will allow them to collaborate and communicate business requirements in a semantically consistent and understandable manner, and then reflect the potential impact of those requirements on the alignment of the business process and IT infrastructure.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin